Temporal and Geographic Clustering of Polyomavirus-Associated Olfactory Tumors in 10 Free-Ranging Raccoons (Procyon lotor). (July 2014) - Giannitti, F.; Higgins, R. J.; Pesavento, P. A.; Cruz, F. Dela; Clifford, D. L.; Piazza, M.; Struckhoff , A. Parker; Valle, L. Del; Bollen, A. W.; Puschner, B.; Kerr, E.; Gelberg, H.; et al.
Reports of primary nervous system tumors in wild raccoons are extremely rare. Olfactory tumors were diagnosed postmortem in 9 free-ranging raccoons from 4 contiguous counties in California and 1 raccoon from Oregon within a 26-month period between 2010 and 2012. We describe the geographic and temporal features of these 10 cases, including the laboratory diagnostic investigations and the neuropathologic, immunohistochemical, and ultrastructural characteristics of these tumors in the affected animals. All 9 raccoons from California were found within a localized geographic region of the San Francisco Bay Area (within a 44.13-km radius). The tight temporal and geographic clustering and consistent anatomic location in the olfactory system of tumor types not previously described in raccoons (malignant peripheral nerve sheath tumors and undifferentiated sarcomas) strongly suggest either a common cause or a precipitating factor leading to induction or potentiation of neuro-oncogenesis and so prompted an extensive diagnostic investigation to explore possible oncogenic infectious and/or toxic causes. By a consensus polymerase chain reaction strategy, a novel, recently reported polyomavirus called raccoon polyomavirus was identified in all 10 tumors but not in the normal brain tissue from the affected animals, suggesting that the virus might play a role in neuro-oncogenesis. In addition, expression of the viral protein T antigen was detected in all tumors containing the viral sequences. We discuss the potential role of raccoon polyomavirus as an oncogenic virus.